Evaluation of modified Ni/ZrO2 catalysts for hydrogen production by supercritical water gasification of oil-containing wastewater. (26th July 2018) - Kou, Jiajing; Xu, Jialing; Jin, Hui; Guo, Liejin; Zhang, Deming; Cao, Wen
Abstract: Supercritical water gasification (SCWG) technology is a clean and cost-effective conversion technology due to its unique chemical and physical properties. However, the unique properties also lead to instability and inactivity for the pure Ni/ZrO2 catalyst in SCWG process. In this work, we investigated the effect of second metal addition on the catalytic performance by modifying Ni/ZrO2 catalysts with different promoters (Co, Ce, La, Y, Mg), which prepared by a single-step sol-gel method. The analysis results of catalysts by XRD, SEM and automatic micropore & chemisorption analyzer showed that Ce, Y, La may be helpful promoters to stabilize the structure of ZrO2 . Compared to the non-catalytic experiment, all the catalysts showed significantly higher activities in the SCWG reaction. Among all catalysts, Ni-Co/ZrO2 exhibited excellent activity, which achieved the highest carbon gasification efficiency (CE) and highest hydrogen yield. Additionally, two key factors, concentration and temperature, were also investigated for the optimum conditions, and the maximum carbon gasification efficiency (CE) of 98.8% was achieved at 600 °C with the Ni-Co/ZrO2 catalyst. Highlights: Ni/ZrO2 catalysts by a single-step sol-gel method were successfully prepared. Modified Ni/ZrO2 catalysts were active for SCWG of oil-containing wastewater. Ce, Y, La were helpful promoters to improve the stability of Ni/ZrO2 catalysts. Ni-Co/ZrO2 catalyst achieved the maximum CE of 98.8% at 600°C in SCW.